Correction: Conceptual design of tetraazaporphyrin- and subtetraazaporphyrin-based functional nanocarbon materials: electronic structures, topologies, optical properties, and methane storage capacities. Issue 30 (19th July 2017) - Belosludov, Rodion V.; Rhoda, Hannah M.; Zhdanov, Ravil K.; Belosludov, Vladimir R.; Kawazoe, Yoshiyuki; Nemykin, Victor N.
Abstract : Correction for 'Conceptual design of tetraazaporphyrin- and subtetraazaporphyrin-based functional nanocarbon materials: electronic structures, topologies, optical properties, and methane storage capacities' by Rodion V. Belosludov et al., Phys. Chem. Chem. Phys., 2016, 18, 13503–13518.